Pengaruh Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Biaya Operasional Terhadap Pendapatan Operasional (BOPO) Terhadap Likuiditas Yang Diukur Dengan Loan to Deposit Ratio Pada PT. Bank Mandiri (Persero) Tbk - Subaktiar Subaktiar; Ujang Abdullah; Radiah Radiah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to analyze and test the influence of CAR, NPL, BOPO on LDR PT. Bank Tabungan Negara Indonesia Tbk. This type of research is explanatory research. The sample used in this research was PT. Bank Mandiri (Persero) Tbk published its financial reports for the 2006-2013 period. Data collection techniques are library research and field research techniques. This research uses descriptive analysis, classical assumption tests and multiple linear regression for data analysis with the help of the Eviews 8 program. From the analysis test results it is known that the CAR, BOPO and NPL ratios have no influence on the LDR ratio during the 2006-2013 period.